2015
DOI: 10.1097/bcr.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function Following Burn Injuries

Abstract: Sexual function is a profound facet of the human personality. Burns due their sudden and devastating nature can have longstanding effects on intimate function by virtue of physical sequelae as well as alterations in body image and perceived desirability. A considerable number of patients encounter problems with intimate function in burns rehabilitation; nevertheless, the topic appears to be poorly addressed in specialist centers worldwide. Review of the literature suggests that a number of parameters can affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The results of the present study suggest an association, albeit weak, between burn size and sexual relationships post-burn. The importance of engaging in sexual relationships during recovery has been studied previously 36,37 and has been established as an important aspect of community participation and psychological rehabilitation. 38 Ohrtman et al found that concerning sexual activity, the burn survivor population does not differ significantly in comparison to a non-burn adult population.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study suggest an association, albeit weak, between burn size and sexual relationships post-burn. The importance of engaging in sexual relationships during recovery has been studied previously 36,37 and has been established as an important aspect of community participation and psychological rehabilitation. 38 Ohrtman et al found that concerning sexual activity, the burn survivor population does not differ significantly in comparison to a non-burn adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the topic received renewed interest in the literature [31,32], but there is still scant evidence providing knowledge on risk factors such as inter-personal factors and scar characteristics. A first step to anticipate fear and avoidance among partners may be assisting the partner in touching the scars or applying a moisturizing cream on the scars before discharge from hospital [33]. It is important that health professionals are aware of these problems, are open to discuss these problems, and are able to offer prompt support or refer to specialized help.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of sexual function following burn injury details some of the themes in the literature associated with poor sexual function following burn injury. 27,28 Issues with impaired ability to achieve orgasm can be associated with post-traumatic stress disorder, other psychological conditions, or even medications related to the treatment of these conditions. These conditions may be associated with hormone disruption or a hyperarousal state, interfering with the normal arousal phase and the androgenic-mediated emission phase of orgasm.…”
Section: Sexual Relationshipsmentioning
confidence: 99%